Burials as identity statements. Some remarks about North-Thracian funerary phenomenon in the 4th—3rd centures BC - Sîrbu, V.; Duţescu, M.; Ştefan, D. (Археологія і давня історія України, 2009)
Due to their inventory, on may consider the burials from Agighiol, Peretu and Mogilanskata Mogila - Vratsa as some of the most spectacular examples within the Thracian area.